A coordenação pedagógica e os ambientes de aprendizagens na educação infantil - Moreira, Karen Eloá Silva (Universidade do Vale do Rio dos Sinos, 2022)
This dissertation aims to analyze the practices of pedagogical coordination that contribute to the promotion of creative, instigating learning environments that enhance participation, autonomy, rich and respectful experiences for children in kindergarten. By means of the established criteria, the empirical field researched was composed of three schools of Early Childhood Education at SESC/RS. In this way, a school in the metropolitan region and two in the interior of the state of Rio Grande do Sul were listed, which made it possible to highlight the scope of the institution's activities, as well as to consider the building structures that were built or that were renovated to carry out the service. to the children, a fact that occurred after the year 2006. From the theoretical framework it was possible to propose a dialogue about the conception of children, of childhood, as well as about the pedagogical coordination and learning environments in the kindergarten school. The methodological approach used in the research is of a qualitative nature, the production of data took place through narrative interviews with the pedagogical coordinators, followed by document analysis, supported by the school regiment, the pedagogical proposal and the photographs that made up the contextualization of the schools. In the analysis and production of data, a set of actions and efforts employed by the pedagogical coordinators were identified, related to favoring environments that allow children to learn in an autonomous, creative, welcoming and respectful way. Finally, in this sense, it was possible to state that the pedagogical coordinators in their school contexts have been developing practices and making efforts, in order to favor and promote a spatial configuration through learning environments in schools. However, limitations were also found that make the advancement and consolidation of learning environments unfeasible. For this, a proposal for educational intervention was elaborated, in order to build pedagogical indicators capable of guiding and consolidating a school configuration that promotes the right of children to live and learn in powerful, instigating and creative environments.
Keywords: Educação infantil; Ambientes de aprendizagens; Coordenação pedagógica; Pedagogia da infância; Criança e direitos; Early childhood education; Learning environments; Pedagogical coordination; Childhood pedagogy; Child and rights; ACCNPQ::Ciências Humanas::Educação